2007
DOI: 10.1002/hlca.200790028
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Synthesis of Highly Substituted Perhydropyrrolizines, Perhydroindolizines, and Pyrrolidines: Inhibition of the Peptidyl‐Prolyl cis/trans Isomerase (PPIase) Pin1

Abstract: In this paper, we describe the synthesis and biological evaluation of highly substituted perhydropyrrolizines that inhibit the peptidyl-prolyl cis/trans isomerase (PPIase) Pin1, an oncogenic target. The enzyme selectively catalyzes the cis/trans isomerization of peptide bonds between a phosphorylated serine or threonine, and proline, thereby inducing a conformational change. Such structural modifications play an important role in many cellular events, such as cell-cycle progression, transcriptional regulation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 59 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…In the future, it is important to investigate the possible involvement of Pin1 in atherosclerosis. There are several Pin1-targeted drugs, but most of them bind to the PPIase domain of Pin1 (29,30). To manipulate the Pin1-mediated regulation of PPAR␥, the WW domain, rather than the PPIase domain, must be targeted by drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, it is important to investigate the possible involvement of Pin1 in atherosclerosis. There are several Pin1-targeted drugs, but most of them bind to the PPIase domain of Pin1 (29,30). To manipulate the Pin1-mediated regulation of PPAR␥, the WW domain, rather than the PPIase domain, must be targeted by drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent chemical analysis revealed that (AE )-1 (and a large number of related imides) are unstable in even mildly basic solution and that the succinimide moiety undergoes rapid and regioselective ring opening by formation of (AE )-2. [2,18] The pK a of the carboxylate group (4.0) in (AE )-2 could be determined by potentiometric titration.…”
Section: Variation Of the S1 Pocket Vectormentioning
confidence: 99%
“…The resulting lone pair dipole interacts with the CO dipole and influences the peptide bond rotation during isomerization . Furthermore, the transition state is stabilized by the interaction between the N–H of the following peptide bond with the lone pair of the sp 3 N. , This isomerization can be catalyzed by peptidyl–prolyl cis–trans isomerases. …”
Section: Introductionmentioning
confidence: 99%